PAR‐3 controls endothelial planar polarity and vascular inflammation under laminar flow. (17th July 2018) - Hikita, Takao; Mirzapourshafiyi, Fatemeh; Barbacena, Pedro; Riddell, Meghan; Pasha, Ayesha; Li, Mengnan; Kawamura, Takuji; Brandes, Ralf P; Hirose, Tomonori; Ohno, Shigeo; Gerhardt, Holger; Matsuda, Michiyuki; et al.
Abstract: Impaired cell polarity is a hallmark of diseased tissue. In the cardiovascular system, laminar blood flow induces endothelial planar cell polarity, represented by elongated cell shape and asymmetric distribution of intracellular organelles along the axis of blood flow. Disrupted endothelial planar polarity is considered to be pro‐inflammatory, suggesting that the establishment of endothelial polarity elicits an anti‐inflammatory response. However, a causative relationship between polarity and inflammatory responses has not been firmly established. Here, we find that a cell polarity protein, PAR‐3, is an essential gatekeeper of GSK3β activity in response to laminar blood flow. We show that flow‐induced spatial distribution of PAR‐3/aPKCλ and aPKCλ/GSK3β complexes controls local GSK3β activity and thereby regulates endothelial planar polarity. The spatial information for GSK3β activation is essential for flow‐dependent polarity to the flow axis, but is not necessary for flow‐induced anti‐inflammatory response. Our results shed light on a novel relationship between endothelial polarity and vascular homeostasis highlighting avenues for novel therapeutic strategies. Synopsis: Along the direction of flow, spatial activation of RhoA/Rho‐kinase distributes the PAR‐3/PKCλ and the GSK3β/PKCλ complexes in a mutually exclusive manner in endothelial cells. This process is important for GSK3β activation controlling inflammatory response via regulating NF‐κB localization. The PAR‐3/PKCλ and GSK3β/PKCλ complexes are distributed in a mutual exclusive manner in endothelial cells along the direction of flow. The spatially antagonized localization of polarity complexes is regulated by RhoA/Rho‐kinase controlling GSK3β activation and thereby EC polarity. While activation of GSK3β is necessary for p65 nuclear localization, spatial distribution of active GSK3β is not essential for endothelial inflammatory responses. Abstract : Along the direction of flow, spatial activation of RhoA/Rho‐kinase distributes the PAR‐3/PKCλ and the GSK3β/PKCλ complexes in a mutually exclusive manner in endothelial cells. This process is important for GSK3β activation controlling inflammatory response via regulating NF‐κB localization.